Priority setting at the clinical level: the case of nusinersen and the Norwegian national expert group - Magelssen, Morten (BMC Med Ethics, 2021)
BACKGROUND: Nusinersen is one of an increasing number of new, expensive orphan drugs to receive authorization. These drugs strain public healthcare budgets and challenge principles for resource allocation. Nusinersen was introduced in the Norwegian public healthcare system in 2018. A national expert group consisting of physicians was formed to oversee the introduction and continuation of treatment in light of specific start and stop criteria. METHODS: We have studied experiences within the expert group with a special emphasis on their application of the start and stop criteria, rationing of treatment, and experienced moral dilemmas. A research interview with six members of the national expert group was performed, then analysed with manifest content analysis. The analysis was supplemented with publically available sources on priority setting and the process leading up to the introduction of nusinersen and the establishment of the expert group. RESULTS: Sixty-six patients have received treatment within the first 25 months since the national expert group’s establishment. Treatment has not been discontinued for any patient. No patients under 18 years of age have been denied treatment, as those who were referred at this age were all deemed to fulfill the start criteria. The expert group has, however, increased geographical treatment equity and facilitated important cooperation at the national level. Furthermore, it has enhanced open and critical discussions of both medical issues and new ethical dilemmas. CONCLUSION: Although facilitating equal access to treatment for SMA patients, the national expert group has not discontinued treatment for any patient. It is suggested that in order for clinicians to be able to ration care for individual patients, they require both adequate support and sufficient formal authority. Start and stop criteria need to be re-evaluated as more knowledge and experience are gained regarding the treatment. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12910-021-00623-5.